Induction : processes of inference, learning, and discovery - Holland, John H. (John Henry), 1929-2015 (Computational models of cognition and perception., 1986)
Two psychologists, a computer scientist, and a philosopher have collaborated to present a framework for understanding processes of inductive reasoning and learning in organisms and machines. Theirs is the first major effort to bring the ideas of several disciplines to bear on a subject that has been a topic of investigation since the time of Socrates. The result is an integrated account that treats problem solving and induction in terms of rulebased mental models. Induction is included in the Computational Models of Cognition and Perception Series. A Bradford Book.